Impact of quality as well as quantity of skeletal muscle on outcomes after liver transplantation. Issue 11 (November 2014) - Hamaguchi, Yuhei; Kaido, Toshimi; Okumura, Shinya; Fujimoto, Yasuhiro; Ogawa, Kohei; Mori, Akira; Hammad, Ahmed; Tamai, Yumiko; Inagaki, Nobuya; Uemoto, Shinji
<x xml:space="preserve">Abstract</x> Intramuscular fat accumulation has come to be associated with loss of muscle strength and function, one of the components of sarcopenia. However, the impact of preoperative quality of skeletal muscle on outcomes after living donor liver transplantation (LDLT) is unclear. The present study evaluated the intramuscular adipose tissue content (IMAC) and psoas muscle mass index (PMI) in 200 adult patients undergoing LDLT at our institution between January 2008 and October 2013. Correlations of IMAC with other factors, overall survival rates in patients classified according to IMAC or PMI, and risk factors for poor survival after LDLT were analyzed. IMAC was significantly correlated with age (r = 0.229, P = 0.03) and PMI (r = −0.236, P = 0.02) in males and with age (r = 0.349, P < 0.001) and branched‐chain amino acid (BCAA)‐to‐tyrosine ratio (r = −0.250, P = 0.01) in females. The overall survival rates in patients with high IMAC or low PMI were significantly lower than those for patients with normal IMAC or PMI (P < 0.001, P < 0.001, respectively). Multivariate analysis showed that high IMAC [odds ratio (OR) = 3.898, 95% confidence interval (CI) = 2.025‐7.757, P < 0.001] and low PMI (OR = 3.635, 95% CI = 1.896‐7.174, P < 0.001) were independent risk factors for death after LDLT. In conclusion, high IMAC and low PMI were closely involved with posttransplant mortality. Preoperative quality and quantity of skeletal muscle could be incorporated into new selection criteria for LDLT. Perioperative nutritional therapy and rehabilitation could be important for good outcomes after LDLT. Liver Transpl 20:1413‐1419, 2014. © 2014 AASLD.